A management model of university social responsibility from the stakeholders perspective - Vásquez Torres, María del Carmen; Tavizón Salazar, Arturo (2021)
Internationally, university social responsibility has become a trend that higher education institutions have adopted models or indicators recommended by different organizations, but they are only theoretical models. This statistical and empirical model is a new way to justify which strategies are the most useful and most impactful. The main purpose is a new management model of university social responsibility analyzed to enhance the performance of university students, and the effect that university social responsibility factors have through the actions of higher education institutions in northeastern Mexico. The methodology used was quantitative, descriptive and predictive using multi-variable techniques of structural equations. The sample was 776 students, with which it is possible to prove that the performance of university stakeholders is influenced by the culture of legality of the students as well as their integral formation and by the projects related to the environment and sustainability as well as their application in university and professional life. A contribution is generated to the management of university social responsibility by identifying which factors are the most important to obtain the most significant impact for the stakeholders.